Vitamin D Supplementation in the Treatment of Chronic Heart Failure: A Meta‐analysis of Randomized Controlled Trials. Issue 1 (28th September 2015) - Jiang, Wei‐Long; Gu, Hai‐Bo; Zhang, Yu‐Feng; Xia, Qing‐Qing; Qi, Jia; Chen, Jian‐Chang
ABSTRACT: Background: In recent years, there has been growing evidence that vitamin D deficiency is associated with the development and progression of chronic heart failure (CHF). Hypothesis: Additional supplementation of vitamin D may have protective effects in patients with CHF. Methods: We searched PubMed, Embase, and Cochrane databases through June 2015 and included 7 randomized controlled trials that investigated the effects of vitamin D on cardiovascular outcomes in patients with CHF. Then, we performed a meta‐analysis of clinical trials to confirm whether vitamin D supplementation is beneficial in CHF patients. The weighted mean difference (WMD) and 95% confidence interval (CI) were calculated using fixed‐ or random‐effects models. Results: Our pooled results indicated that additional supplementation of vitamin D was not superior to conventional treatment in terms of left ventricular ejection fraction, N‐terminal pro‐B‐type natriuretic peptide, and 6‐minute walk distance. Moreover, vitamin D supplementation was associated with significant decreases in the levels of tumor necrosis factor‐α (WMD: −2.42 pg/mL, 95% CI: −4.26 to −0.57, P < 0.05), C‐reactive protein (WMD: −0.72 mg/L, 95% CI: −1.42 to −0.02, P < 0.05), and parathyroid hormone (WMD: −13.44 pg/mL, 95% CI: −21.22 to −5.67, P < 0.05). Conclusions: Vitamin D supplementation may decrease serum levels of parathyroid hormone and inflammatory mediators in CHF patients, whereas it has no beneficial effects on improvement of left ventricular function and exercise tolerance.